Estimating the impact of access to infrastructure and extension services in rural Nepal - Dillon, Andrew; Sharma, Manohar; Zhang, Xiaobo (International Food Policy Research Institute, 2011)
During the period of Nepal’s ninth Five-Year Plan (1997–2002), agricultural growth in the predominantly rural society was disappointing. The recent peace process, however, gives the country new opportunities to develop its economy with less interference due to internal conflict. This research monograph investigates how Nepal might seize these opportunities by increasing agricultural growth and poverty reduction through improvements in roads, irrigation, and rural extension. The authors evaluate the impact of public investments in these areas by using two types of data and methodology: a hedonic approach that relates access to public infrastructure and services to land value and a panel of household-level data on consumption, poverty, and income. The hedonic methodology suggests a positive relationship between investments in irrigation and extension and household welfare, although the panel data approach suggests otherwise. This result reinforces the importance of methodology in evaluating rural investments. Rural roads yielded more clear-cut findings, however: both approaches agree that investment there has a positive relationship with household welfare, as measured in land values, consumption growth, poverty reduction, or agricultural income growth. The authors recommend increased public investments in rural roads, irrigation, and extension, as well as further research into precisely how infrastructure and services affect rural households’ welfare and how their effectiveness can be improved. This monograph will be useful to policymakers, researchers, and others concerned with Nepal’s future development.